2020
DOI: 10.1111/ejn.14709
|View full text |Cite
|
Sign up to set email alerts
|

Electrophysiological responses to regularity show specificity to global form: The case of Glass patterns

Abstract: The holographic weight of evidence model (van der Helm & Leeuwenberg, J Math Psychol, 35, 1991, 151; van der Helm & Leeuwenberg, Psychol Rev, 103, 1996, 429) estimates that the perceptual goodness of moiré structures (Glass patterns), irrespective of their global form, is comparable to that of reflection symmetry. However, both behavioural and neuroscience evidences suggest that certain Glass forms (i.e. circular and radial structures) are perceptually more salient than others (i.e. translation structures) and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
6
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 76 publications
1
6
0
Order By: Relevance
“…The latter study showed that when (irregular) parts of a symmetric shape are shown at different points in time, the visual system can retain information and integrate it with newer information. The output of this integration was evidenced by an ERP component known as Sustained Posterior Negativity (SPN) (Makin et al, 2016;Rampone & Makin, 2020). In stimuli were presented within a static reference frame.…”
Section: Discussionmentioning
confidence: 99%
“…The latter study showed that when (irregular) parts of a symmetric shape are shown at different points in time, the visual system can retain information and integrate it with newer information. The output of this integration was evidenced by an ERP component known as Sustained Posterior Negativity (SPN) (Makin et al, 2016;Rampone & Makin, 2020). In stimuli were presented within a static reference frame.…”
Section: Discussionmentioning
confidence: 99%
“…This relationship between local and global form gives versatility to the pattern, as various aspects of the local form can be changed while maintaining the overall global form, such as the spatial frequency content ( Dakin & Bex, 2001 ), density ( Dakin, 1997a ), colour ( Mandelli & Kiper, 2005 ), and contrast ( Dakin & Bex, 2001 ; Lin et al., 2017 ; Wilson et al., 2004 ). This versatility allowed to investigate how the visual system pools local orientation signals into a global form percept ( Chen, 2009 ; Dakin & Bex, 2001 ; Nankoo et al., 2012 ) and the neural substrates underlying the perception of different spatial configurations ( Krekelberg et al., 2005 ; Makin et al., 2016 ; Ostwald et al., 2008 ; Rampone & Makin, 2020 ).…”
mentioning
confidence: 99%
“…In addition, lesions to V4 impair Glass pattern perception [20]. The steadystate VEP response to reflectional symmetry and Glass patterns is comparable [21,22], and both regularities generate the same SPN [12,23]. SPNs generated by reflection and Glass patterns are shown in Figure 1A.…”
Section: Introductionmentioning
confidence: 97%